Evaluation of total knee mechanics using a crouching simulator with a synthetic knee substitute. (May 2016) - Lowry, Michael; Rosenbaum, Heather; Walker, Peter S
Mechanical evaluation of total knees is frequently required for aspects such as wear, strength, kinematics, contact areas, and force transmission. In order to carry out such tests, we developed a crouching simulator, based on the Oxford-type machine, with novel features including a synthetic knee including ligaments. The instrumentation and data processing methods enabled the determination of contact area locations and interface forces and moments, for a full flexion–extension cycle. To demonstrate the use of the simulator, we carried out a comparison of two different total knee designs, cruciate retaining and substituting. The first part of the study describes the simulator design and the methodology for testing the knees without requiring cadaveric knee specimens. The degrees of freedom of the anatomic hip and ankle joints were reproduced. Flexion–extension was obtained by changing quadriceps length, while variable hamstring forces were applied using springs. The knee joint was represented by three-dimensional printed blocks on to which the total knee components were fixed. Pretensioned elastomeric bands of realistic stiffnesses passed through holes in the block at anatomical locations to represent ligaments. Motion capture of the knees during flexion, together with laser scanning and computer modeling, was used to reconstruct contact areas on the bearing surfaces. A method was also developed for measuring tibial component interface forces and moments as a comparative assessment of fixation. The method involved interposing Tekscan pads at locations on the interface. Overall, the crouching machine and the methodology could be used for many different mechanical measurements of total knee designs, adapted especially for comparative or parametric studies.